Developing WisDOT standard specifications for helical piles - Corson, Cory R. (University of Wisconsin--Stout, 2019)
The definition and integration of universal provisions for new standard bid items in WisDOT Standard Specifications is recognized as a challenging assignment. Before a proposed specification can be implemented, delineating material, construction, and compensatory language that can be universally applied across all projects must be established. The following work initiates discussion and research for implementing the first-ever standard specification for helical piles to be included in WisDOT's Standard Specification. For the purpose of the study, data was collected from two special provisions accepted by WisDOT, one IowaDOT special provision, and three proprietary specifications created by independent helical pile manufactures. From this pool of information, research was conducted to verify the appropriateness of the various material requirements and the construction techniques to meet WisDOT's needs. Furthermore, the proposed standard was compared against like-kind specifications to ensure procurement and material specifications were analogous. The research contained in this work results in a baseline specification for which WisDOT may conduct further research and product testing. The research does not prove or disprove engineer calculations and should carefully be reviewed before acceptance. The end product of this work is intended to provide designers and contractors with adequate guidance to design and construct helical piles.
Keywords: Construction industry; Gearing, Spiral